Review of Physical Fitness of Grade V Students at SD Negeri 2 East Gorom Sbt Regency - Endang Kairoty; Emma Rumahlewang; S. Divinubun (Peneliti.net, 2022)
This study aims to determine the level of physical fitness of fifth grade students at SD Negeri 2 East Gorom, SBT District. Physical fitness is an important element that is very influential in the PJOK learning process, this is in line with the notion of physical fitness according to Hidayat in Suhartoyo 2019, Physical fitness does not only have a good influence on the development of affective aspects in students, but with good physical fitness will also be able to give effect to learning outcomes. Students who have a high level of physical fitness will also get high academic achievement results. The design of this study uses a non-experimental research type through a descriptive quantitative , aims to collect data using the TKJI test. This research was carried out at SD Negeri 2 Gorom Timur, SBT District with a total population of 20 students and a total sample of 20 students. Sampling was carried out using the Random Sampling technique, the data analysis technique used the Presentation Formula. The results of the research conducted showed that the Physical Fitness of Class V Students at SD Negeri 2 Gorom Timur Kab SBT there were 0% (0 samples) had very good physical fitness, 11% (11 samples), had good physical fitness, 5% (5 sample) had moderate physical fitness, 4% (4 samples) had moderate physical fitness, and 0% (0 samples) had very poor physical fitness